Romantic Ideation, Partner-Seeking, and HIV Risk among Young Gay and Bisexual Men - Bauermeister, José A. (2011)
Structural changes in the acceptability of same-sex relationships may provide young gay and bisexual men (YGBM) with opportunities to develop expectations about their ideal future relationships. Expectations about the future may act as a promotive factor in youths’ lives and reduce HIV risk-taking behaviors; however, few studies have examined the relationship between ideation of a future relationship and sexual behaviors of YGBM. In this study, we examined the relationship between romantic ideation (i.e., intimacy, passion, and commitment) and number of sexual partners in a sample of young men (N = 431; M age = 21.49 years; 88% self-identified as gay) who reported using the Internet to meet other men. Using multivariate Poisson regressions, we found a negative association between commitment and number of partners for unprotected sex, both receptive and insertive, in the past two months. We found similar results when we examined the association between relationship exclusivity and number of partners. These associations persisted after accounting for age, race/ethnicity, sexual identity, and hours spent seeking casual and romantic partners online. We found no significant association between number of partners and ideation of an intimate or passionate relationship, respectively. We discuss the implications of our findings and conclude that there is a need to consider and include YGBM's expectations about the future in on-going HIV prevention programs.